2019
DOI: 10.1007/s00424-019-02310-2
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial atrophy in Alzheimer’s disease

Abstract: Astrocytes, a class of morphologically and functionally diverse primary homeostatic neuroglia, are key keepers of neural tissue homeostasis and fundamental contributors to brain defence in pathological contexts. Failure of astroglial support and defence facilitate the evolution of neurological diseases, which often results in aberrant synaptic transmission, neurodegeneration, and death of neurones. disease (AD) astrocytes undergo complex and multifaceted metamorphoses ranging from atrophy with loss of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 164 publications
(215 reference statements)
6
86
0
2
Order By: Relevance
“…Our findings of pronounced morphological atrophy in human iPSCs parallel recent demonstration of similar morphological atrophy in iPSC-derived astrocytes generated from early familial and late sporadic AD patients [45]. Morphological atrophy of astrocytes is arguably associated with neuronal damage (due to failed homeostatic support) and aberrant synaptic connectivity manifest in neurodegenerative and psychiatric diseases (for a review see [42]). In many cases, astrocytic atrophy precedes cell death and neuronal degeneration.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings of pronounced morphological atrophy in human iPSCs parallel recent demonstration of similar morphological atrophy in iPSC-derived astrocytes generated from early familial and late sporadic AD patients [45]. Morphological atrophy of astrocytes is arguably associated with neuronal damage (due to failed homeostatic support) and aberrant synaptic connectivity manifest in neurodegenerative and psychiatric diseases (for a review see [42]). In many cases, astrocytic atrophy precedes cell death and neuronal degeneration.…”
Section: Discussionsupporting
confidence: 85%
“…Subsequent studies revealed that functional exhaustion and loss of astroglial homeostatic support are dominant glial contribution to the PD, and the special definition of "dysfunctional" astrocytes has been introduced [38,39]. Astroglial asthenia, atrophy and loss of homeostatic and neuroprotective capacities were noted in aging [40] and in various neurodegenerative and neuropsychiatric diseases [41,42]; astroglial atrophy thus represents a defined class of astrogliopathies [43].…”
Section: Discussionmentioning
confidence: 99%
“…therapeutic action remains unclear. At the early stages, both Alzheimer's disease and epilepsy are associated with astrocyte atrophy 29,74 . The growth of astrocytic processes induced by CR counteracts this pathological remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…These conceptualisations, however, are based on relatively thin data when it comes to astrogliosis; the ubiquitous gliosis is further questioned by well documented presence of dystrophic microglia in the aged human brains (Conde and Streit, 2006). There are substantial arguments for a decrease in functional capacities of neuroglial cells in ageing, with glial dystrophy and paralysis facilitating neurodegeneration (Streit et al, 2020;Verkhratsky et al, 2015;Verkhratsky et al, 2019).…”
Section: Shrinkage Of Astrocytic Territorial Domains In the Old Agementioning
confidence: 99%